PENGARUH ORIENTASI PASAR, KELENGKAPAN PRODUK DAN SALURAN DISTRIBUSI TERHADAP KINERJA PEMASARAN PRODUK CUSSONS BABY PADA PT.MATAKAR KENDARI - Aminudin, La Ode; Bua, Hasanuddin; Nur, Nofal (-)
This study aims to determine the effect of market orientation, product completeness and distribution channels on the enlargement performance of Cussons Baby products at PT. Matakar Kendari. The sample in this study is 72 outlets that have been registered as customers of PT. Kendari Matakar using multiple linear regression analysis method. Based on the results of statistical calculations, it shows that there is a positive and partially significant influence between the variables of market orientation, product completeness, and distribution channels on the marketing performance of cussons baby products at PT. Matakar Kendari. With the meaning that the better the market orientation, product completeness and distribution channels, the better the marketing performance of cussons baby products at PT Matakar Kendari. Â